Subject and Methodological Competencies in Teachers: Testing the Unified Federal Evaluation Tools - Altynikova N.V; Muzaev A.A (Moscow State University of Psychology and Education, 2019)
The article describes the main approaches to developing and testing the unified federal evaluation tools (UFET) used for studying subject and methodological competencies of teachers in the Russian Federation. The authors propose a level assessment model of teacher competencies based on the professional standard for teachers. Results of the research helped to identify the shortcomings of teacher training which make carrying out professional activities difficult for teachers. The article describes the terms of using UFET in the procedures of teacher certification and presents the main developmental directions for the current system of continuing teacher education. The authors argue that applying UFET at different stages of teacher training and professional development may ensure the formation of more effective individual educational routes for every teacher aimed at eliminating their professional deficits and improving the standards of education in general.